Lucerastat, an Iminosugar for Substrate Reduction Therapy: Tolerability, Pharmacodynamics, and Pharmacokinetics in Patients With Fabry Disease on Enzyme Replacement. Issue 4 (28th August 2017) - Guérard, Nicolas; Oder, Daniel; Nordbeck, Peter; Zwingelstein, Christian; Morand, Olivier; Welford, Richard W.D.; Dingemanse, Jasper; Wanner, Christoph
Abstract : Lucerastat is a glucosylceramide synthase inhibitor aimed at reducing production of glycosphingolipids (GSLs), including those accumulating in Fabry disease. The safety, tolerability, pharmacodynamics, and pharmacokinetics of oral lucerastat were evaluated in an exploratory study in patients with Fabry disease. In this single‐center, open‐label, randomized study, 10 patients received lucerastat 1, 000 mg b.i.d. for 12 weeks in addition to enzyme replacement therapy (ERT; the lucerastat group). Four patients with Fabry disease received ERT only. Eight patients reported 17 adverse events (AEs) in the lucerastat group. No clinically relevant safety abnormalities were observed. The mean (SD) levels of the plasma GSLs, glucosylceramide, lactosylceramide, and globotriaosylceramide, were significantly decreased from baseline in the lucerastat group (‐49.0% (16.5%), ‐32.7% (13.0%), and ‐55.0% (10.4%), respectively). Lucerastat 1, 000 mg b.i.d. was well tolerated in patients with Fabry disease over 12 weeks. A marked decrease in plasma GSLs was observed, suggesting clinical potential for lucerastat in patients with Fabry disease.